2014
DOI: 10.17511/ijmrr.2014.i05.11
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Correlates of Bronchial Asthma in Children in a Slum of Meerut - A Cross-Sectional Study

Abstract: Introduction: In India, an estimated 57,000 deaths were attributed to Asthma in 2004 & it was seen as one of the leading cause of morbidity and mortality (WHO 2004). The range of prevalence of Bronchial asthma in children in India varied from 2% to 20%. So far, no community based studies have been conducted in Western Uttar Pradesh to find out the prevalence of bronchial asthma in children. The present study is an effort in that direction. Objective: To determine the prevalence of bronchial asthma among childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…Another South Indian study has reported such independent association of 6-9 years age group with bronchial asthma among school going children [21]. Male gender was also found to be an independent risk factor for childhood asthma, in similar with other studies [13,22]. This male predominance is due to the relatively narrow airways of boys which persist till adolescence.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Another South Indian study has reported such independent association of 6-9 years age group with bronchial asthma among school going children [21]. Male gender was also found to be an independent risk factor for childhood asthma, in similar with other studies [13,22]. This male predominance is due to the relatively narrow airways of boys which persist till adolescence.…”
Section: Discussionsupporting
confidence: 83%
“…Kumar et al [30] have reported a lower prevalence of asthma in children with smoke outlets in their houses, though there was no association with the type of fuel used. We could not find any significant association regarding exposure to mice, cockroach, livestock and pet animals with risk of childhood asthma, which was similar to several studies [22,31]. In contrary, a study from Beijing have reported increased risk of asthma for those having both a dog and a cat as pets or for finding both cockroaches and rats inside their houses [32].…”
Section: Discussionsupporting
confidence: 81%
“…In respiratory parcel, lower respiratory lot contamination is one of the main normal infection happen during childhood. (George et al, 2014) LRTIs are a steady and an inescapable medical condition which force a gigantic weight on the general public. They being regular purposes behind interview and hospitalization (Rabe et al, 2000) The patients present with a wide range of sicknesses which range from minor self restricting ailments to conceivably dangerous infections (Juniper et al, 2004).…”
Section: Introductionmentioning
confidence: 99%